2017
DOI: 10.3233/jad-161274
|View full text |Cite
|
Sign up to set email alerts
|

Neural Dynamics of Multiple Object Processing in Mild Cognitive Impairment and Alzheimer’s Disease: Future Early Diagnostic Biomarkers?

Abstract: The aim of this study was to investigate the behavioral and electrophysiological dynamics of multiple object processing (MOP) in mild cognitive impairment (MCI) and Alzheimer's disease (AD), and to test whether its neural signatures may represent reliable diagnostic biomarkers. Behavioral performance and event-related potentials [N2pc and contralateral delay activity (CDA)] were measured in AD, MCI, and healthy controls during a MOP task, which consisted in enumerating a variable number of targets presented am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This influential model predicts that the over-recruitment of brain areas serves as compensatory activity against deterioration processes ( Reuter-Lorenz et al, 2000 ; Cabeza et al, 2002 ). Compensatory mechanisms, however, may also be lateralized in the brain as is the case of the contralateral delay activity (CDA), an EEG neural marker of the multiple object enumeration process that was found to be able to capture hemispheric lateralization in older adults ( Bagattini et al, 2017 ; Sander et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This influential model predicts that the over-recruitment of brain areas serves as compensatory activity against deterioration processes ( Reuter-Lorenz et al, 2000 ; Cabeza et al, 2002 ). Compensatory mechanisms, however, may also be lateralized in the brain as is the case of the contralateral delay activity (CDA), an EEG neural marker of the multiple object enumeration process that was found to be able to capture hemispheric lateralization in older adults ( Bagattini et al, 2017 ; Sander et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Three age-matched groups of participants were included in this study: 14 patients with a clinical diagnosis of mild AD (seven females, mean age = 74.9, SD = 6.0, range = 63–83), 15 amnesic patients with MCI (six females, mean age = 74.5, SD = 5.9, range = 60–81), and 14 healthy elderly controls (HC; 9 females, mean age = 70.9, SD = 3.8, range = 67–82). Data from these participants were included in Bagattini et al (2017) and partly in Brignani et al (2018) . Clinical diagnosis of AD and amnesic MCI was done by expert neurologists or geriatricians addressing medical history, clinical examination, neuropsychological testing, and imaging results such as computed tomography, MRI, or PET.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review paper, 22% of reviewed studies between MCI and CU groups reported a significant difference in N200 amplitude, while the rate was 18% between ADD and CU groups (Paitel et al, 2021). More specifically, some studies reported smaller N200 amplitude in both MCI and ADD groups over the CU groups (Fernandez et al, 2013;Wang et al, 2013;Bagattini et al, 2017), while some others stated no difference in N200 between MCI and CU groups (Cespón et al, 2015a;Mudar et al, 2016) or between CU and ADD groups (Bagattini et al, 2017). The abovemixed results might be due to the different variants of the oddball tasks used as the kind of stimuli, the inter-stimulus intervals, the task duration, the level of required attention to the stimuli and experimental conditions, and the kind of subject's responses required during ERP recordings (Morrison et al, 2019).…”
Section: Event-related Potentials (Erps)mentioning
confidence: 99%
“…These theories were examined and discussed not just using behavioral methods but also with neuroimaging methods (e.g., in Cutini, Scatturin, Basso Moro, & Zorzi, 2014;Leibovich, Henik, & Salti, 2015;Piazza et al, 2002), with abnormal populations (Ashkenazi et al, 2013;Bagattini et al, 2017;Dehaene & Cohen, 1994;Gagnon, Mottron, Bherer, & Joanette, 2004;Mazza, 2017), and in other modalities.…”
Section: Subitizing In the Visual Domainmentioning
confidence: 99%